The relationship between facial symmetry and social behaviour in free-ranging long-tailed macaques (Macaca fascicularis). - Lin, XiaoTian. (2010)
Primate faces provide critical information for friendship, with facial symmetry allowing display of superior quality. Following findings on increased facial symmetry related to beneficial social interactions in humans, this study hypothesized that such relationship exists for primates. We analyzed facial symmetry of 26 long-tailed macaques (10 males, 16 females) using three various measurements (6-line discrepancy, 9-line discrepancy, and Symmeter™). Data was collected on social behaviour, which included proximity, grooming received, and dominance rank. In general, facial symmetry did not have significant positive relation with social behaviour. Decreased need for interaction amongst kin, emotional book-keeping and definition of friendship in primates may have greater influence on social behaviour than facial symmetry. I address the need for valid measurements of facial symmetry.